Facile synthesis of a novel, efficient, reusable inorganic adsorbent from volcanic rock powder wastes and its application for the removal of dyes and metals from water (2024)
A new, efficient, and reusable inorganic adsorbent (NP.F) was easily synthesized using volcanic rock powder wastes (NP) as a precursor, with the synthesis of NP.F carried out at 550 ºC and with a ratio of NaOH (alkalinizing) and sample NP equal to 1. The samples were used in batch adsorption to uptake Ag+(aq.), Cu2+(aq.), acid green 16 (AG 16), and acid red 97 (AR 97) from aqueous solutions at pH 6.53, 5.98, and 2.3, respectively. NP and NP.F were characterized by different analytical techniques, such as XRD, FTIR, BET, TGA/DTG, etc. The adsorption kinetic carried out at 298 K for dye solutions with concentrations ranging from 50 to 200 mg L−1 and metals from 10 to 100 mg L−1 showed that data fit the pseudo-second-order mathematical model with rapid sorption and process equilibrium was reached after 30 min for dyes and 40 min for metal ions. The Sips model proved adequate to represent the adsorption isotherms of metallic ions and the dye AR 97, while the BET model represented the isotherms of the dye AG 16. The NP.F sample showed notable adsorption capacity for all the contaminants studied; for example, the adsorption capacity of the dye AR 97 was 295 mg g−1, while that of the Ag+ ion was 93 mg g−1. Besides, the adsorption of Cu2+(aq.) ion, dyes AG 16, and AR 97 were endothermic, while the adsorption of Ag+(aq.) was exothermic. Furthermore, even after numerous subsequent adsorption cycles, the NP.F sample maintained a high reusability, suggesting that the sample is qualified to be an adsorbent for removing contaminants from liquid effluents. In conclusion, NP.F could be easily converted into an efficient inorganic adsorbent for colorants and metals.